Garranes An Early Medieval Royal Site in South-West Ireland - O'Brien, William (Archaeopress Publishing, 2021)
Ringforts were an important part of the rural settlement landscape of early medieval Ireland (AD 400-1100). While most of those circular enclosures were farmsteads, a small number had special significance as centres of political power and elite residence, also associated with specialized crafts. One such 'royal site' was Garranes in the mid-Cork region of south-west Ireland. In 1937, archaeological excavation of a large trivallate ringfort provided evidence of high-status residence during the fifth and sixth centuries AD. The site had workshops for the production of bronze ornaments, with glass and enamel working as well as indications of farming. Pottery and glass vessels imported from the Mediterranean world and Atlantic France were also discovered. That trade with the Late Roman world is significant to understanding the introduction of Christianity and literacy in southern Ireland at that time.This monograph presents the results of an interdisciplinary project conducted 2011-18, where archaeological survey and excavation, supported by various specialist studies, examined this historic landscape. Garranes is a special place where archaeology, history and legend combine to uncover a minor royal site of the early medieval period. The central ringfort has been identified as Rath Raithleann, the seat of the petty kingdom of Uí Echach Muman, recalled in bardic poetry of the later medieval period. Those poems attribute its foundation to Corc, a King of Munster in the fifth century AD, and link the site closely to Cian, son-in-law of Brian Bóruma, and one of the heroes of Clontarf (AD 1014). This study provides new evidence to connect the location of Rath Raithleann to high-status occupation at Garranes during the fifth and sixth centuries, and explores its legendary associations in later periods.Includes contributions from Michelle Comber, Ian Doyle, Lenore Fischer, Kevin Kearney, Susan Lyons, Tim Mighall and Douglas Borthwick, Margaret Mannion, Ignacio Montero-Ruiz and Mercedes Murillo-Barroso, Róisín Nic Cnáimhín, Cian Ó Cionnfhaolaidh, James O'Driscoll, Edward O'Riordain, and Orla-Peach Power.